2008
DOI: 10.1128/jb.01067-07
|View full text |Cite
|
Sign up to set email alerts
|

Global Genomic Analysis of Pseudomonas savastanoi pv. savastanoi Plasmids

Abstract: Pseudomonas savastanoi pv. savastanoi strains harbor native plasmids belonging to the pPT23A plasmid family (PFPs) which are detected in all pathovars of the related species Pseudomonas syringae examined and contribute to the ecological and pathogenic fitness of their host. However, there is a general lack of information about the gene content of P. savastanoi pv. savastanoi plasmids and their role in the interaction of this pathogen with olive plants. We designed a DNA macroarray containing 135 plasmid-borne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
73
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 45 publications
3
73
1
Order By: Relevance
“…The IAA operon and the iaaL gene reside on a plasmid (pIAA) in P. savastanoi strains isolated from oleander galls (5,7,8,14); however, the direction of iaaL transcription has been determined to be opposite to IAA operon transcription (14). In contrast, most olive isolates have been reported to carry all three IAA genes on the chromosome (5,8,32). In a recent study, P. savastanoi pv.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The IAA operon and the iaaL gene reside on a plasmid (pIAA) in P. savastanoi strains isolated from oleander galls (5,7,8,14); however, the direction of iaaL transcription has been determined to be opposite to IAA operon transcription (14). In contrast, most olive isolates have been reported to carry all three IAA genes on the chromosome (5,8,32). In a recent study, P. savastanoi pv.…”
mentioning
confidence: 99%
“…Recently, a global genomic analysis of P. savastanoi pv. savastanoi plasmids allowed the identification of several putative virulence factors in the olive pathogen, including several type III secretion system protein effectors and a variety of genes encoding known Pseudomonas syringae virulence factors (32).…”
mentioning
confidence: 99%
“…Tumor development is dependent on bacterial production of phytohormones indoleacetic acid and cytokinins (Comai & Kosuge, 1980;Iacobellis et al, 1994;Rodríguez-Moreno et al, 2008;Smidt & Kosuge, 1978;Surico et al, 1985). Besides, recent results have revealed that Psv strains contain two copies of all the genes involved in indoleacetic acid synthesis (Matas et al, 2009;Pérez-Martínez et al, 2008). It has been reported that olive knots are also dependent on the hrp/hrc genes (Sisto et al, 2004), which encode the biosynthesis of a functional Type III Secretion System (TTSS).…”
Section: Biology Of Infectionmentioning
confidence: 99%
“…It has been reported that olive knots are also dependent on the hrp/hrc genes (Sisto et al, 2004), which encode the biosynthesis of a functional Type III Secretion System (TTSS). Recently, remarkable progress has been made in research into several aspects of the host-pathogen interaction of the causal agent of olive knot (Pérez-Martínez et al, 2008;Matas, 2010;Pérez-Martínez et al, 2010). Several putative virulence factors in Psv have been identified, including TTSS protein effectors and a variety of genes encoding known P. syringae virulence determinants (Pérez-Martínez et al, 2008).…”
Section: Biology Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation